Calculations of Energy Athlete Based on Android Application - Afif, Ucu Muhammad; Millah, Haikal; Purnama, Selly (Journal of Physical Education and Sports, 2018)
This study aims to build energy-based athlete calculator application needs, by knowing the energy needed every day, can find out how much energy is released each day and can set the number of calories eaten by knowing the number of calories issued. This research uses research and development method. At the start of opening the app, the user enters the application next the application menu consisting of the next two menu buttons that are the application usage tutorial and calorie counting. In the input menu data calorie needs calculation there are several columns that must be filled by the user are: name, age, weight, height, gender, activity category, sport type, frequency of exercise in every week, duration of exercise per day in minutes, exercise, weekly exercise frequency, exercise duration per week. After input data is filled, then press process button to know the result of caloric requirement. Preparation of application of energy needs of athletes based on android stages as follows: Potential and Problems, Data Collection, Product Design, Design Validation, Design Revision, Product Trial, Product Revision, Trial of Use, Product Revision, and Mass Production.